2017
DOI: 10.1002/pen.24767
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous toughening and strengthening of diglycidyl ether of bisphenol‐a using epoxy‐ended hyperbranched polymers obtained from thiol‐ene click reaction

Abstract: Epoxy‐ended hyperbranched polymers (EHBP) has become a class of additives for diglycidyl ether of bisphenol‐A (DGEBA), but it is tedious processes retards wide application. Here, we prepared EHBP by a thiol‐ene click reaction between thiol‐terminated hyperbranched polyesters and allyl glycidyl ether and modified DGEBA. The incorporation of EHBP significantly enhanced the toughness and strength of DGEBA. The mechanical properties of EHBP/DGEBA composite increased remarkably with the increasing EHBP molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In addition, the HBP could penetrate the molecular chains of the DGEBA matrix due to its small hydrodynamic volume for increasing interactions between molecular chains during curing and reinforced tensile and flexural strength. Similar results can also be observed in other research studies regarding the use of epoxy-ended HBPs [ 130 , 133 , 134 ]. Miao et al [ 135 , 136 ] synthesized an epoxy-ended hyperbranched polyether sulphone as a modifier for DGEBA resin cured with triethylenetetramine, which did not phase-separate.…”
Section: Thermomechanical Characteristicssupporting
confidence: 90%
“…In addition, the HBP could penetrate the molecular chains of the DGEBA matrix due to its small hydrodynamic volume for increasing interactions between molecular chains during curing and reinforced tensile and flexural strength. Similar results can also be observed in other research studies regarding the use of epoxy-ended HBPs [ 130 , 133 , 134 ]. Miao et al [ 135 , 136 ] synthesized an epoxy-ended hyperbranched polyether sulphone as a modifier for DGEBA resin cured with triethylenetetramine, which did not phase-separate.…”
Section: Thermomechanical Characteristicssupporting
confidence: 90%
“…Polysilsesquioxanes can be further functionalized by attaching a variety of functional organic groups, providing the resultant polymer nanocomposites with excellent properties. 9–12 Using epoxy-functionalized cage-like polyhedral oligomeric silsesquioxane (POSS) to reinforce epoxy thermosets is of interest. 13,14 The rigid silica cages provide strength and the epoxy groups of POSS improve interaction with the matrix and also provide polymer chains with moderate flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of hyperbranched polymeric FRs has solved this problem, as they not only have the properties of dendritic structures, such as highly branched molecular structures and abundant end structures, 43 but also have the characteristics of easy synthesis, 44 low viscosity and high fluidity, and can be uniformly dispersed in polymeric materials with good compatibility, 44 showing good prospects for FR applications. [45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…Although the dendritic cyclotriphosphazene derivatives do not have the problem of poor compatibility with polymer materials, their synthesis process is too tedious and complicated, and they must undergo multiple steps to achieve the required functionality. The emergence of hyperbranched polymeric FRs has solved this problem, as they not only have the properties of dendritic structures, such as highly branched molecular structures and abundant end structures, 43 but also have the characteristics of easy synthesis, 44 low viscosity and high fluidity, and can be uniformly dispersed in polymeric materials with good compatibility, 44 showing good prospects for FR applications 45–47 . Chen et al synthesized a P/N/Si/B hyperbranched FR with a rigid‐flexible structure (PTDOB) to improve the fire safety and mechanical properties of epoxy resins, and the results demonstrated that the addition of PTDOB could effectively improve the flame retardancy and mechanical properties of EP 48 .…”
Section: Introductionmentioning
confidence: 99%